MORPHOLOGICAL STUDIES ON THE THORACIC, LUMBAR, SACRAL AND COCCYGEAL VERTEBRAE IN SPOTTED DEER (Axis axis) - C. V. Rajani; I. S. Sajitha; M. Pradeep; J.J.Chungath (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Morphology of the thoracic, lumbar, sacral and coccygeal vertebrae of spotted deer was studied using three specimens. The number of vertebrae in thoracic, lumbar, sacral and coccygeal region was thirteen, six, four and twelve respectively. The bodies of the thoracic vertebrae showed a prominent ventral crest from the seventh onwards as in cattle. The articular facets for ribs were concave and quite separate in the first to sixth thoracic vertebrae but were close together in the succeeding vertebrae and even fused on the thirteenth thoracic vertebra. The height of spinous process increased up to the fourth thoracic vertebrae then it decreased to the ninth and the last three had equal height. The caudal slope of spinous process increased up to the tenth vertebra but the twelfth and thirteenth vertebrae had vertical spinous processes and formed the anticlinal vertebrae as in small ruminants. Only eleventh to thirteenth thoracic vertebrae possessed distinct articular processes. The rounded mammillary processes were seen next to the transverse processes except in twelfth and thirteenth vertebrae where they formed mammilioarticular processes. In the lumbar region, the transverse diameter and caliber of the vertebral canal increased from the first to the last. The transverse process of the first vertebra was the shortest; length increased up to the fifth and in the sixth it was shorter as recorded in cattle. Each lumbar vertebra presented two strongly curved cranial articular processes with fused mamillary processes on lateral aspect. The triangular sacrum was formed by fusion of four segments as in sheep and differed from cattle and goat where five segments fused to form sternum. The first two coccygeal vertebrae were typical and haemal processes were absent.